Calvin and the Duty of Guardians to Resist: a Comment - Stein, Peter (The journal of ecclesiastical history, 1981)
Mr Lloyd's argument is based on the fact that Calvin, when discussing the magistrates' duty to protect the commons against a tyrannical ruler, describes them as tutores. He suggests that Calvin was specifically referring to the tutela of Roman law.Tutela in Roman law was the power allowed by the law to a ‘guardian’ over a free person—normally one who had been left independent by the death of his father, in whose power he had been—who by reason of age was unable to look after his own affairs. The tutor's function was confined to safeguarding the property interests of the child, and did not extend to control over his personal welfare or education. Tutela lasted in the case of a boy until puberty (the age of fourteen years) but thereafter it was usual for a young man to have a curator to look after his property and he was subject to cura or curatio until he was twenty-five. The tutor was liable for both fraud and negligence, and the liability was enforced by two actions. One, the crimen suspecti tutoris, could be brought by anyone other than the ward himself, to obtain the removal of the tutor for misconduct; the other, the actio tutelae, was brought by the former ward, after the completion of the tutela, for any misconduct committed during it.